REVITALISASI KAWASAN LEMBAH TAMANSARI MELALUI PEMBERDAYAAN ORGANISASI MASYARAKAT - Cahyani, Diah (TERAS)
The Development of an area which based on social organization have been being in various region in Indonesia. In this context, basically give awareness and opportunity for society which taking a part in development process. Organizational construction is aimed for ability by giving education to grow with strong motivation and enthusiasm to society in order to taking a part with actively in development. Others, is growing ability and independence to associate the aspiration of society in national development. The goal of this study is analyze the organization in area of study function optimally, can earn powered as media of development. Study conducted in area of Lembah Tamansari, Cipaganti village ( focus study of RW 02 and RW 04), Coblong Sub district, Bandung, with method of observation and interview to local elite figure and the organizational perpetrator of existing society. There are social organization in this area , that is LPM, PKK and Karang Taruna. After analyze data by using process of a group theory and the goal of social organization, to be obtained the picture of social organization effectiveness which contribute to environmental problems of settlements. The social organization in study area, dont have own ability to finish environmental problems of study area. Performance which is not optimal caused by limited amount organization human skills and quality.